Membangkitkan Jiwa Ekonomi Kreatif Melalui Pelatihan Penghitungan Laba Rugi dan BEP Pada Siswa SMP IT Al- Azhar Mojokerto - Fitra Ria Silvida (Jurnal Abdi Anjani, 2023)
Providing material related to the creative economy to SMPIT Al Azhar students is expected to awaken the students' entrepreneurial spirit which is directed towards the creative economy. Community service begins with providing material related to socialization of the creative economy, analysis of the creative economic situation in Mojokerto Regency, providing material related to business plans, calculating profit and loss and BEP (BREAK EVENT POINT), then ends with providing business capital of IDR 100,000 to 5 a team of students with the most interesting business plan and one that can most realistically be run with that amount of capital. After that, assistance and monitoring of the business was carried out for the next month by resource persons and the school regarding the running of this creative economy business. The results obtained are 5 creative economic businesses that have been run by 5 student teams, earning a profit of 10-20% in the current one month period. This creative economy business unit is carried out and run within the school. So for students who do not receive capital assistance, you can be sure that these students at least know and understand that there is a creative economy that they can see as an opportunity to accommodate creative ideas and also make money. Apart from that, students are also able to calculate BEP (Break Event Point) and business profit and loss in a simple format but still does not reduce its important es